1996
DOI: 10.1073/pnas.93.16.8374
|View full text |Cite
|
Sign up to set email alerts
|

The full-length leptin receptor has signaling capabilities of interleukin 6-type cytokine receptors.

Abstract: The leptin receptor (OB-R) is a single membrane-spanning protein that mediates the weight regulatory effects of leptin (OB protein). The mutant allele (db) of the OB-R gene encodes a protein with a truncated cytoplasmic domain that is predicted to be functionally inactive. Several mRNA splice variants encoding OB-Rs with different length cytoplasmic domains have been detected in various tissues. Here we demonstrate that the full-length OB-R (predominantly expressed in the hypothalamus), but not a major natural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
505
2
19

Year Published

1997
1997
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 749 publications
(543 citation statements)
references
References 32 publications
17
505
2
19
Order By: Relevance
“…The OSMRP and the OB-R are related to gp130 in primary structure (23.3% and 20.7% overall amino acid identity, respectively) and in modular structure, featuring both Ig-like and FN III domains (Hibi et al, 1990;Tartaglia et al, 1995;Mosley et al, 1996). While the OB-R and gp130, at least in part, activate overlapping intracellular signaling molecules, gp130 does not form part of the receptor-complex of leptin (Baumann et al, 1996a).…”
Section: The Il-6 Signal Transduce< Gp130mentioning
confidence: 99%
“…The OSMRP and the OB-R are related to gp130 in primary structure (23.3% and 20.7% overall amino acid identity, respectively) and in modular structure, featuring both Ig-like and FN III domains (Hibi et al, 1990;Tartaglia et al, 1995;Mosley et al, 1996). While the OB-R and gp130, at least in part, activate overlapping intracellular signaling molecules, gp130 does not form part of the receptor-complex of leptin (Baumann et al, 1996a).…”
Section: The Il-6 Signal Transduce< Gp130mentioning
confidence: 99%
“…structure, consisting of four interconnected antiparallel a-helices, is highly similar to members of the long-chain helical cytokines, such as interleukin-6 (IL-6), IL-11, IL-12, and granulocyte colony-stimulating factor. 17,18 As an endocrine hormone, leptin is synthesized mainly by adipose tissue and, more particularly, by differentiated mature adipocytes. Circulating levels and adipose tissue mRNA expression of leptin are proportionate to the body mass index (BMI) and the body fat mass.…”
Section: Introductionmentioning
confidence: 99%
“…In the recent years, accumulating evidence has established the role of leptin as a growth factor that modulates immune responses [2,3]. The structure of leptin has high similarity to members of the long-chain helical cytokines such as IL-6, IL-11, IL-12, G-CSF, leukemia inhibitory factor and oncostatin [4,5]. Several studies have revealed an important role for leptin in regulating lymphopoiesis and hematopoiesis [1,2,[6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…In relation to the important function of leptin in immune responses, leptin receptor (Ob-R) expression has been found not only in the central nervous system but also in peripheral lymphoid tissues and hematopoietic stem cells [2,8,12]. Encoded by the diabetes (db) gene, the Ob-R is a member of the class I cytokine receptors, which have the signaling capability of IL-6-type cytokine receptors [4]. Ob-R mRNA gives rise to six different forms of the receptor by alternative splicing, but only the long isoform (Ob-Rb) has been recognized to be of importance in leptin-mediated signaling [1].…”
Section: Introductionmentioning
confidence: 99%